Animal, vegetable, miracle : a year of food life - Kingsolver, Barbara; Hopp, Steven L., 1954-; Kingsolver, Camille, 1987- (New York ; Toronto : HarperPerennial, 2008)
Follows the author's family's efforts to live on locally- and home-grown foods, an endeavor through which they learned lighthearted truths about food production and the connection between health and diet.
Called home -- Waiting for asparagus: late March -- Springing forward -- Stalking the vegetannual -- Molly mooching: April -- The birds and the bees -- Gratitude: May -- Growing trust: mid-June -- Six impossible things before breakfast: late June -- Eating neighborly: late June -- Slow food nations: late June -- Zucchini larceny: July -- Life in a red state: August -- You can't run away on harvest day: September -- Where fish wear crowns: September -- Smashing pumpkins: October -- Celebration days: November-December -- What do you eat in January? -- Hungry month: February-March -- Time begins.
On cover: P.S. insights, interviews & more.
Includes bibliographical references (p. [364]-370)
Keywords: Kingsolver, Barbara; Hopp, Steven L., -- 1954-; Farm life -- Appalachian Region, Southern -- Anecdotes; Country life -- Appalachian Region, Southern -- Anecdotes; Agriculture -- Appalachian Region, Southern -- Anecdotes; Food habits -- Appalachian Region, Southern -- Anecdotes